Congenital absence of the vas deferens with hypospadias or without hypospadias: Phenotypic findings and genetic considerations - Fang, Jianzheng; Wang, Xiaoyi; Sun, Xueping; Cui, Yugui; Diao, Feiyang; Yang, Xiaoyu (Frontiers in Genetics, 2022)
Congenital absence of the vas deferens (CAVD) is an important cause of obstructive azoospermia. Mutations of CFTR and ADGRG2 caused the majority of CAVD. Despite this, 10-20% CAVD patients remain without a clearly genetic diagnosis. Herein, the CFTR and ADGRG2 genes were firstly sequenced by Sanger sequencing in 50 CAVD patients. Whole-exome sequencing (WES) was employed to further identify potential novel genetic causes in CAVD with hypospadias. In total, 29 of 50 CAVD patients carried at least one CFTR mutation, but no ADGRG2 mutation were found. 5T was found to be the most frequent variants in our CAVD populations. Seven CAVD patients with hypospadias were further analyzed by WES. No homozygous or compound heterozygous mutations related to disorders of sex development (DSDs) or male infertility were identified by WES. The CAVD with hypospadias have smaller testicular volume (9.71±2.14ml vs. 14.45±2.93ml, p<0.001) and higher FSH level (FSH: 7.28±3.91 IU/L vs. 4.24±1.96 IU/L, p=0.027) than CAVD without hypospadias. It is worth noting that neither CFTR or ADGRG2 mutation nor homozygous or compound heterozygous gene mutations were identified in seven CAVD with hypospadias. However, nine heterozygous or hemizygous mutations were selected as potential pathogenic gene in CAVD with hypospadias. In conclusion, CFTR variants, especially 5T, play a major role in the Chinese CAVD population. The CAVD with hypospadias have relatively lower testicular spermatogenesis, suggesting it seems to have a different genetic basis or pathogenic factor from cystic fibrosis /CAVD or unilateral renal agenesis/CAVD.